2020
DOI: 10.1128/mcb.00257-19
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase HRD1 Promotes Lung Tumorigenesis by Promoting Sirtuin 2 Ubiquitination and Degradation

Abstract: The NAD-dependent histone deacetylase sirtuin 2 (SIRT2) plays critical roles in mitosis and cell cycle progression and recently was shown to suppress tumor growth and to be downregulated in several types of cancers. However, the underlying mechanism of SIRT2 downregulation remains unknown. In this study, using bioinformatics, gene expression profiling, protein overexpression approaches, and cell migration assays, we showed that E3 ubiquitin ligase 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Synoviolin (SYVN1), an evolutionarily conserved endoplasmic reticulum‐resident E3 ligase, is the central component of a complex facilitating degradation of misfolded proteins during the ubiquitin‐proteasome‐dependent process of endoplasmic reticulum‐associated degradation [ 14 , 15 ]. SYVN1 participates in biological events in several cancer types by regulating the ubiquitination and degradation of P53 [ 16 ], insulin‐like growth factor‐I receptor [ 17 ], and Sirtuin 2 [ 18 ]. Heat shock proteins (HSPs), which could help cancer cells survive and obtain an invasive phenotype, always function as molecular chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…Synoviolin (SYVN1), an evolutionarily conserved endoplasmic reticulum‐resident E3 ligase, is the central component of a complex facilitating degradation of misfolded proteins during the ubiquitin‐proteasome‐dependent process of endoplasmic reticulum‐associated degradation [ 14 , 15 ]. SYVN1 participates in biological events in several cancer types by regulating the ubiquitination and degradation of P53 [ 16 ], insulin‐like growth factor‐I receptor [ 17 ], and Sirtuin 2 [ 18 ]. Heat shock proteins (HSPs), which could help cancer cells survive and obtain an invasive phenotype, always function as molecular chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT2 directly binds to transcription factor EB, to regulate acute shear stress-induced cell apoptosis by regulating the release of autophagy components and exosomes, which contributes to the suppression of tumorigenesis and the metastasis of NSCLC ( 71 ). A recent study demonstrated that SIRT2 was readily degraded via homologous recombination repair-mediated ubiquitination in NSCLC ( 67 ), supporting the anticancer function of SIRT2 in this disease.…”
Section: Emerging Roles Of Sirt2 In Nsclcmentioning
confidence: 85%
“…Conflicting studies have nevertheless shown that SIRT2 expression is downregulated in NSCLC and that SIRT2 can inhibit tumor growth ( 49 , 67 ). Zhu et al ( 68 ) reported that deacetylation of aldo-keto reductase family 1 member C1 (AKR1C1) by SIRT2 inhibited the binding of AKR1C1 to STAT3, therefore decreasing the transcriptional activity of STAT3 and inhibiting migration of NSCLC cells.…”
Section: Emerging Roles Of Sirt2 In Nsclcmentioning
confidence: 99%
“…Ubiquitination assay was performed as previously described [ 35 ]. In brief, cells were lysed with a high concentration of SDS lysis buffer, denatured, immunoprecipitated with appropriate antibodies, and subjected to immunoblotting.…”
Section: Methodsmentioning
confidence: 99%